2013
DOI: 10.1161/hypertensionaha.113.01648
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1, Oxidative Stress, and Endogenous Angiotensin II

Abstract: Hypertension during preeclampsia is associated with increased maternal vascular sensitivity to angiotensin II (ANGII). This study was designed to determine mechanisms whereby agonistic autoantibodies to the ANGII type I receptor (AT1-AA) enhance blood pressure (MAP) and renal vascular sensitivity to ANGII during pregnancy. First, we examined MAP and renal artery resistance index (RARI) in response to chronic administration of ANGII or AT1-AA or AT1-AA+ANGII in pregnant rats compared to control pregnant rats. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 23 publications
6
88
0
Order By: Relevance
“…Another possibility is that pathophysiological levels of ET-1 (or ET-1 ) and/or heightened expression of ET A receptors on vascular smooth muscle lead to overactivation of ET A receptors, thus overwhelming the physiological activation of the endothelial ET B -NO vasodilatory pathway by RLN, leading to renal vasoconstriction. Circulating AT1-AA could directly agonize the AT1 receptor on the afferent arteriole and synergize with circulating AII, thereby impairing renal function (19). Furthermore, this synergy may contribute to the increase in systemic AII pressor response in PE (76,201).…”
Section: Possible Mechanisms Of Renal Impairment In Preeclampsiamentioning
confidence: 99%
“…Another possibility is that pathophysiological levels of ET-1 (or ET-1 ) and/or heightened expression of ET A receptors on vascular smooth muscle lead to overactivation of ET A receptors, thus overwhelming the physiological activation of the endothelial ET B -NO vasodilatory pathway by RLN, leading to renal vasoconstriction. Circulating AT1-AA could directly agonize the AT1 receptor on the afferent arteriole and synergize with circulating AII, thereby impairing renal function (19). Furthermore, this synergy may contribute to the increase in systemic AII pressor response in PE (76,201).…”
Section: Possible Mechanisms Of Renal Impairment In Preeclampsiamentioning
confidence: 99%
“…Furthermore, AT 1 -AA and sFlt-1 play a significant role in the development of endothelial dysfunction and hypertension in PE and have been found to correlate with PE severity in patients (15,25,30,43,60,64,65,67,69,71,72). AT 1 -AA infusion induces many pathophysiological characteristics of PE, including increased blood pressure, vascular resistance, ET-1, and sFlt-1 (8,35). Although the contribution of immune factors in the pathogenesis of preeclampsia is well established, immune therapy in preeclamptic women is limited by the potential for teratogenic effects of many anti-inflammatory and antihypertensive drugs.…”
mentioning
confidence: 99%
“…Moreover, infusion of AT 1 -AA into pregnant rats induced a hypertensive response that seemed to be via an endothelin-1-dependent mechanism. 45,46 In another study, injection of AT 1 -AA into pregnant rats induced symptoms consistent with preeclampsia, including hypertension, proteinuria, and intrauterine growth retardation that was associated with the upregulation of hypoxia-inducible factor-1α and endothelin-1. 47 In this case, however, the phenotypic effect was only observed when the antibody transfer was performed in combination with angiotensin II, 47 that is, not when transferred alone as in other studies.…”
Section: Autoantibodies To the At 1 R In Preeclampsiamentioning
confidence: 99%
“…47 In this case, however, the phenotypic effect was only observed when the antibody transfer was performed in combination with angiotensin II, 47 that is, not when transferred alone as in other studies. 45,46 Therefore, a wealth of studies have demonstrated a key role for AT 1 -AA in the pathophysiology of preeclampsia. The efficacy of the AFHYESQ epitope-blocking peptide in abolishing the AT 1 -AA functional response has been established, thus raising the possibility of epitope peptide therapy as a tenable therapeutic strategy to treat preeclampsia.…”
Section: Autoantibodies To the At 1 R In Preeclampsiamentioning
confidence: 99%